A Review on the Current Status and Influencing Factors of Anaerobic Digestion - Wang, Luyao; Sun, Wen (International Journal of Electric Power and Energy Studies, 2025)
Anaerobic digestion (AD) is a well-established biological process that converts organic matter into biogas, primarily methane, under anaerobic conditions. With the growing emphasis on renewable energy and waste management, AD has gained significant attention as a sustainable technology. This review summarizes the current status of anaerobic digestion research, focusing on its microbial ecology, key process parameters, and technological advancements. The influencing factors discussed include pH and alkalinity, organic loading rate (OLR), hydraulic retention time (HRT), temperature, mixing intensity, nutrient balance, and the presence of inhibitory substances. The review also highlights the development of anaerobic reactor systems and the application of modern molecular techniques in understanding microbial dynamics. Finally, the potential of AD in addressing energy and environmental challenges is emphasized.